Pattern of oral lesions in multidrugs resistant tuberculosis patient and the management: a case report - Djou, Rahmatia; Setiadhi, Riani (Hasanuddin University, 2020)
Objectives: to describe the pattern of oral lesions in MDR TB patient and the management. Methods: A 42-year-old man with history of TB since 8 months before and MDR TB since 1 month. The patient complained of sore tongue since 2 weeks before, accompanied with white plaque on the tongue which could be scrapped off leaving erythema areas. Intraoral examination showed multiple ulcers at lateral and dorsum of the tongue, white plaques on the tongue, buccal mucosa, labial mucosa, and palate. Swab examination from the tongue showed a positive result for Gram-positive Bacillus Bacteria. Tuberculosis ulcers and oral candidiasis were the diagnosis, so that the given treatment were nystatin oral suspension and 0.2% chlorhexidine gluconate mouthwash. Result: Ulcer and white plaques improved within 3 weeks. Conclusion: The clinical manifestation of oral tuberculosis lesions usually non-specific and sometimes similar with other lesions, making it difficult to be diagnosed